TIME HISTORY ANALYSIS PADA STRUKTUR BANGUNAN YANG MENGGUNAKAN BASE ISOLATOR - Misdi, Misdi; Hamzah, Amir (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2025)
Base isolators are designed to protect structures from earthquake impacts by decoupling horizontal ground motion from the building. This technology is widely applied to bridges, buildings, and critical facilities due to its efficiency in reducing damage risks. This study aims to evaluate the effectiveness of base isolators in minimizing dynamic structural responses to earthquakes. Numerical simulations were conducted to compare the performance of structures with and without base isolators, focusing on maximum acceleration, velocity, and displacement. The results indicate that base isolators reduce maximum acceleration by 75.1%, velocity by 74.83%, and displacement by 34.79%. Therefore, base isolators have proven to significantly enhance structural resilience against earthquakes. These findings provide practical insights for designing safer and more earthquake-resistant buildings